2017
DOI: 10.3390/s17081748
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip High-Finesse Fabry-Perot Microcavities for Optical Sensing and Quantum Information

Abstract: For applications in sensing and cavity-based quantum computing and metrology, open-access Fabry-Perot cavities—with an air or vacuum gap between a pair of high reflectance mirrors—offer important advantages compared to other types of microcavities. For example, they are inherently tunable using MEMS-based actuation strategies, and they enable atomic emitters or target analytes to be located at high field regions of the optical mode. Integration of curved-mirror Fabry-Perot cavities on chips containing electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…Fabry–Pérot (FP) etalon is considered to be a promising choice for the volume sensing application due to its simple structure and growing performance [ 16 ]. Some recent research demonstrated that open-access optical cavities with high Q factor and low mode volume can be achieved by utilizing micro-scale curved-mirrors [ 55 ], or even a spherical mirror on a fiber tip-end and an assorted planar mirror [ 56 ].…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabry–Pérot (FP) etalon is considered to be a promising choice for the volume sensing application due to its simple structure and growing performance [ 16 ]. Some recent research demonstrated that open-access optical cavities with high Q factor and low mode volume can be achieved by utilizing micro-scale curved-mirrors [ 55 ], or even a spherical mirror on a fiber tip-end and an assorted planar mirror [ 56 ].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Microfluidics has achieved great progress recently due to its own excellent performance in fluidic handling [ 7 , 8 , 9 ], micro-environment control [ 10 , 11 , 12 ] and signal amplification [ 13 , 14 ]. By integrating advanced micro- and nano-optical systems with well-developed microfluidics technology, optofluidics has ushered in a new era of lab-on-a-chip functionality [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], including biochemical sensing with optical measurement [ 23 ], optofluidic imaging [ 24 ], and light-driven manipulation [ 25 , 26 ]. In the case of RI sensing, many valuable review papers such as Fan’s [ 27 ] have found that synergistic integration creates unique characteristics that promote the performance and function of biological/chemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Such cavities take advantage of absorptionlimited dielectric mirror coatings to achieve very high reflectivity [218,219], and offer full spatial and spectral tunability by positioning the mirrors, but their cm-scale size leads to large mode volumes and limited scalability. By miniaturizing the parabolic mirrors, these drawbacks can be mitigated, with micron scale geometries achieving mode volumes on the order of λ 3 [220]. Moreover, the small size of the micromirrors enables parallelized fabrication processes [220][221][222] and direct integration with optical fibers [107,223].…”
Section: Open Fabry-perot Microcavitiesmentioning
confidence: 99%
“…By miniaturizing the parabolic mirrors, these drawbacks can be mitigated, with micron scale geometries achieving mode volumes on the order of λ 3 [220]. Moreover, the small size of the micromirrors enables parallelized fabrication processes [220][221][222] and direct integration with optical fibers [107,223].…”
Section: Open Fabry-perot Microcavitiesmentioning
confidence: 99%
“…Disordered photonic chips can achieve sub- resolution by exploring scattering patterns, but suffer from a limited wavelength range [ 11 ]. Despite the improved resolution, wavelength-selective devices using digital planar holography [ 12 , 13 ], photonic crystal slot waveguide [ 14 ], microring resonator combined with a diffraction grating [ 15 , 16 ], multimode spiral waveguide [ 17 ], cylindrical Fabry–Perot (FP) cavity [ 18 , 19 ] and double ring resonator [ 20 ] are suitable to be built laterally on a wafer, which complicates on-chip integration with the light source and the detector.…”
Section: Introductionmentioning
confidence: 99%